Microshear bonding effectiveness of different dentin regions - Anelise F Montagner; Marcos P M Carvalho; Alexandre H Susin (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of this in vitro study was to evaluate the influence of dentin surfaces with different tubule orientation on bond strength of a multimode adhesive system. Materials and Methods: Twenty human molars were selected and prepared in different ways in order to produce different dentin regions. The teeth were randomized (n = 5) according to the application modes of a multimode adhesive system (etch-and-rinse and self-etching) and to the dentin region (occlusal and proximal - 1.5 mm depth from dentinoenamel junction). Cylindrical restorations were performed on dentin with a starch tube. The samples remained immersed in distilled water for 24 h and the microshear bond strength (μSBS) test was performed. The μSBS values were expressed in MPa and analyzed with ANOVA and Tukey's test (P < 0.05). Results: There was no significant difference in the bond strength values between the application modes of the adhesive system (P = 0.19); however, the dentin regions (P < 0.05) significantly affected the μSBS. The proximal dentin presented higher bond strength values than occlusal dentin. Conclusion: The dentin surfaces with different tubule orientation influenced the bonding effectiveness of the adhesive system tested.